BAL Cell Gene Expression Is Indicative of Outcome and Airway Basal Cell Involvement in Idiopathic Pulmonary Fibrosis - Prasse, Antje; Binder, Harald; Schupp, Jonas C.; Kayser, Gian; Bargagli, Elena; Jaeger, Benedikt; Hess, Moritz; Rittinghausen, Susanne; Vuga, Louis; Lynn, Heather; Violette, Shelia; Jung, Birgit; et al. (American journal of respiratory and critical care medicine, 2019)
Idiopathic pulmonary fibrosis (IPF) is a fatal disease with a variable and unpredictable course. To determine whether BAL cell gene expression is predictive of survival in IPF. This retrospective study analyzed the BAL transcriptome of three independent IPF cohorts: Freiburg (Germany), Siena (Italy), and Leuven (Belgium) including 212 patients. BAL cells from 20 healthy volunteers, 26 patients with sarcoidosis stage III and IV, and 29 patients with chronic obstructive pulmonary disease were used as control subjects. Survival analysis was performed by Cox models and component-wise boosting. Presence of airway basal cells was tested by immunohistochemistry and flow cytometry. A total of 1,582 genes were predictive of mortality in the IPF derivation cohort in univariate analyses adjusted for age and sex at false discovery rate less than 0.05. A nine-gene signature, derived from the discovery cohort (Freiburg), performed well in both replication cohorts, Siena (P < 0.0032) and Leuven (P = 0.0033). nCounter expression analysis confirmed the array results (P < 0.0001). The genes associated with mortality in BAL cells were significantly enriched for genes expressed in airway basal cells. Further analyses by gene expression, flow cytometry, and immunohistochemistry showed an increase in airway basal cells in BAL and tissues of IPF compared with control subjects, but not in chronic obstructive pulmonary disease or sarcoidosis. Our results identify and validate a BAL signature that predicts mortality in IPF and improves the accuracy of outcome prediction based on clinical parameters. The BAL signature associated with mortality unmasks a potential role for airway basal cells in IPF.